A novel index for the study of synergistic effects during the co-processing of coal and biomass. (15th February 2017) - Oladejo, Jumoke M.; Adegbite, Stephen; Pang, Cheng Heng; Liu, Hao; Parvez, Ashak M.; Wu, Tao
Highlights: A novel indicator was proposed to quantify the extent of synergy in co-processing. Synergistic interactions are biomass constituents dependent. AAEMs in biomass showed catalytic effect on synergistic interactions. High volatile content demonstrated non-catalytic effect on synergistic interactions. Synergistic interactions can be used to enhance combustion performance. Abstract: In this study, synergistic interaction between coal and biomass and its intensity were investigated systematically using a low rank coal and its blends with different biomass samples at various blending ratios. The catalytic effects of minerals originated from biomass were also studied. It was found that some of the minerals existing in the ash derived from oat straw catalysed the combustions process and contributed to synergistic interactions. However, for the coal and rice husk blends, minimal improvements were recorded even when the biomass and coal blending ratio was as high as 30 wt%. Biomass volatile also influenced the overall combustion performance of the blends and contributed to synergistic interactions between the two fuels in the blends. Based on these findings, a novel index was formulated to quantify the degree of synergistic interactions. This index was also validated using data extracted from literature and showed satisfactory correlation coefficients. It was found that at a blending ratio of 30 wt% oat straw in the blend, the degree of synergistic interaction between coal and oat straw showed an additional SF value of 0.25 with non-catalytic and catalytic synergistic effect contributing 0.16 (64%) and 0.09 (36%) respectively. This index could be used in the selection of proper biomass and proper blending ratio for co-firing at coal-fired power stations aiming at improving the combustion performance of poor quality coals via enhancing synergistic interactions during co-processing.